Breast cancer and breast health awareness as an evolving health promotion concept - Plesničar, Andrej (Radiology and oncology (Ljubljana), 2004)
Background. Breast cancer is the most frequent malignant disease in the majority of developed countries. In the last few years the introduction of mammography screening programmes has resulted in an improved survival of breast cancer patients. However, the incidence of the disease in these countries is still on the increase. Present focus on secondary breast cancer prevention activities, consisting of early detection and treatment, cannot ensure a decrease of breast cancer incidence. Improved breast health awarenesscould therefore represent a part of specific health promotion activities aimed at decreasing the incidence of breast cancer. Conclusions. Indeveloped countries breast cancer is a significant health care issue. Secondary breast cancer prevention activities should therefore be complementedby specific health promotion activities in order to reduce its incidence in the future. Primary breast cancer prevention would include healthpromotion activities aimed at enhancement of the individual as well as collective breast health awareness. Properly enlightened members of the influential population groups could attain appropriate changes in the fields of legislation, taxation, customs and commercial regulations that would enablewomen to control their own breast health.
Keywords: breast; Breast neoplasms; Dojka, novotovrbe; dojke; Health promotion; Preprečevanje in nadzor; Prevention and control; Promocija zdravja; rak (medicina)